2018
DOI: 10.1111/isj.12179
|View full text |Cite
|
Sign up to set email alerts
|

Mobile health technology adoption across generations: Narrowing the digital divide

Abstract: Mobile health (m-health) technologies offer many benefits to individuals, organizations, and health professionals alike. Indeed, the utilization of m-health by older adults can foster the development of proactive patients, while also reducing financial burden and resource pressures on health systems. However, the potentially transformative influence of m-health is limited, as many older adults resist adoption leading to the emergence of an age-based digital divide. This study leverages protection motivation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
3
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(161 citation statements)
references
References 73 publications
5
148
3
5
Order By: Relevance
“…Nonetheless, we intend to conduct further research with users and non‐users of wearable technologies in different countries to gain a more thorough understanding of QS technologies' effects and implications. Furthermore, it could be very interesting to examine other profiles of QS users, such as the elderly and people with medical conditions, who use trackers for managing their health, not only for their well‐being (Fox & Connolly, ). Health trackers offer them the opportunity to stay at home instead of going to the hospital or moving to a nursing home, thus improving their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we intend to conduct further research with users and non‐users of wearable technologies in different countries to gain a more thorough understanding of QS technologies' effects and implications. Furthermore, it could be very interesting to examine other profiles of QS users, such as the elderly and people with medical conditions, who use trackers for managing their health, not only for their well‐being (Fox & Connolly, ). Health trackers offer them the opportunity to stay at home instead of going to the hospital or moving to a nursing home, thus improving their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have highlighted that age [69,70] and gender [71] are important moderators when it comes to making a decision whether or not to adopt wearable devices or health apps. While acknowledging the fact that the personal health status could be an additional relevant moderator [72], there have not been many studies that specifically investigated how a person's PLOS ONE condition might affect the adoption behavior of physiolytics.…”
Section: Moderating Effects Of Health Statusmentioning
confidence: 99%
“…Fox and Connolly [9] studied the barriers to older adult use of mobile technology and found that many older adults had concerns about privacy. Barnard et al [10] highlighted the importance of support to older adults when they are learning to use new mobile devices (i.e.…”
Section: Literature Review: Meaningful Access?mentioning
confidence: 99%